2013
DOI: 10.3141/2383-02
|View full text |Cite
|
Sign up to set email alerts
|

Drivers' Perception of Route Alternatives as Indicator for the Indifference Band

Abstract: Although travel time is probably one of the most important attributes in route choice, the shortest time route is often not the preferred route, according to several studies in the literature. This study tries to explain this finding by testing the hypothesis that choice makers may be able to estimate travel times correctly for routes that they prefer but are biased against alternatives even if these are faster. For a few choice sets of routes in the city of Enschede, Netherlands, respondents were asked to cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Empirical research found that the factors considered by travelers in making route choice decisions were not unitary [6]. Numerous attributes were found to be important considerations, including travel time, trip distance, average speed, and the number of traffic signals along the route.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research found that the factors considered by travelers in making route choice decisions were not unitary [6]. Numerous attributes were found to be important considerations, including travel time, trip distance, average speed, and the number of traffic signals along the route.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though travelers occasionally have correct perception of route performance, they may not be willing to switch to the perceived better route; rather, they stick to the habitual choice until its performance is not satisfying. In other words, travelers are not necessarily utility maximizers [6]. Satisfying psychology triggers individuals' behavioral mechanisms in seeking a satisfactory solution instead of the optimal one.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research of the authors addressed the topic of indifference band thresholds by studying the influence of perception bias on route choice, and how route attributes and past decisions affect perception [21,22]. To complement this research, the aim of this paper is to observe the frequency of different choice strategies, to determine how they are influenced by situational variables and to quantify the thresholds associated to the strategies.…”
Section: Objective and Approachmentioning
confidence: 99%
“…That is, people are more likely to attach positive feeling to options they choose and attribute negative features to options they reject (Mather et al, 2003, Henkel andMather, 2007) even if that would be irrational. In terms of travel choices this suggests that travelers have different perceptions of options they frequently use than options they hardly use (Vreeswijk et al 2013). …”
Section: Mobile Sensor Datamentioning
confidence: 99%